Determinants and Consequences of Executive Compensation - Michele Fabrizi (Padova University Press, 2021)
Incentive compensation is a central concern in the relationship between the Chief Executive Officer (CEO) and the board of directors and between the CEO and shareholders. This book presents a focus on four key themes that are salient to the current debate on the consequences and determinants of executive compensation. The first topic discussed in the book relates to the role of regulation on executive compensation. By analyzing a specific regulatory change (i.e. the issuance of SFAS 123R in the U.S.) we discuss how firms adjust the compensation structure of their executives following a regulatory change. Next, the analysis moves to compensation practices in the financial industry, and it investigates to which extent compensation incentives are linked to risk-taking behaviors. Subsequently, the compensation structure of non-CEO executives is examined: Most of the literature in accounting and finance neglects the potential effect of the compensation structure of executives other than the CEO and we show that not necessary all first order effects are captured by the compensation structure of the CEO. Finally, the last chapter provides the reader with a focus on the consequences of executive compensation in driving misbehaviors. In doing so, the analysis focuses on earning management strategies as an example of misbehavior and it empirically investigates to which extent CEO's incentives - specifically equity and risk-taking incentives - model the trade-off among the different strategies available to executives to engage into earning manipulations and mislead external stakeholders. Overall, analyses presented in this book confirm the importance of using a multidisciplinary approach when studying how executive incentives translate into actions and strategies.
Keywords: 650; Management; executive compensation; performance fee; USA; Führungskräfte; Managervergütung; Leistungsentgelt; USA